2022
DOI: 10.3389/fonc.2022.803777
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Photoacoustic Imaging in Radiation Oncology

Abstract: Radiotherapy is recognized globally as a mainstay of treatment in most solid tumors and is essential in both curative and palliative settings. Ionizing radiation is frequently combined with surgery, either preoperatively or postoperatively, and with systemic chemotherapy. Recent advances in imaging have enabled precise targeting of solid lesions yet substantial intratumoral heterogeneity means that treatment planning and monitoring remains a clinical challenge as therapy response can take weeks to manifest on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 149 publications
(191 reference statements)
0
11
0
Order By: Relevance
“…Both oxygenated and deoxygenated Hb exhibit a molar extinction coefficient that is at least one order of magnitude greater than other common chromophores such as lipids at wavelengths between 650 and 900 nm, and spectral unmixing of photoacoustic measurements made with at least two wavelengths within this wavelength range can quantitatively approximate StO 2 values ( 28 ). PAI has the potential to be a scalable tool to enable patient stratification and monitor therapy response ( 29 ). Given the wide utility of ultrasound (US) in clinical imaging of pancreatic tumors, we believe that ultrasound-guided photoacoustic imaging (US-PAI) can simultaneously provide structural (tumor volume and shape) and functional (vascular StO 2 ) information of pancreatic tumors ( 28 , 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both oxygenated and deoxygenated Hb exhibit a molar extinction coefficient that is at least one order of magnitude greater than other common chromophores such as lipids at wavelengths between 650 and 900 nm, and spectral unmixing of photoacoustic measurements made with at least two wavelengths within this wavelength range can quantitatively approximate StO 2 values ( 28 ). PAI has the potential to be a scalable tool to enable patient stratification and monitor therapy response ( 29 ). Given the wide utility of ultrasound (US) in clinical imaging of pancreatic tumors, we believe that ultrasound-guided photoacoustic imaging (US-PAI) can simultaneously provide structural (tumor volume and shape) and functional (vascular StO 2 ) information of pancreatic tumors ( 28 , 30 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…151 Higher oxygen saturation (sO 2 ) could predict tumor response to single-dose radiotherapy, and the sensitivity and early treatment response of some PAI-based radiotherapy were under clinical evaluation (NCT04428515, NCT04110249, and NCT04437030). 152 3.2.2. ÁOH.…”
Section: Radiotherapymentioning
confidence: 99%
“…Hypoxia always happens in late‐stage tumours. Hypoxic tumours are found to be highly aggressive and resistant to chemoradiotherapy because hypoxic tumours require triple the normal radiation dose to achieve the desirable cell death effect as a normal irradiating dose which means that hypoxia is also a key factor in determining the growth of tumour‐induced by MDR 87,88 . Previous studies have revealed that oxygenation in glioma is 10 mmHg compared with normal brain tissue which is 40 mmHg and which may arise from radiation resistance.…”
Section: Tumour Microenvironment Is the Main Medium For The Prolifera...mentioning
confidence: 99%